A Computer-Based Tutor to Teach Nursing Trauma Care That Works as an Adjunct to High-Fidelity Simulation. Issue 2 (February 2021) - Garrison, Christopher M.; Ritter, Frank E.; Bauchwitz, Benjamin R.; Niehaus, James; Weyhrauch, Peter W.
Abstract : Educators are challenged to prepare nurses to care for low-frequency, high-stakes problems such as trauma. Computer-based tutors provide a cost-effective teaching strategy without risking patient safety. Evidence for the efficacy of this type of instruction is limited; thus, we tested the learning outcomes of a tutor on trauma care knowledge with senior nursing students. Participants were randomly assigned to either the tutor or a control condition (textbook learning). Instructional design elements incorporated into the tutor included use of multimedia content, emphasis of key points, frequent quizzing with instant feedback, and unfolding case studies to summarize key concepts. Use of the tutor led to a larger increase in trauma nursing knowledge than use of a textbook. In addition, the knowledge was retained as well as book-based learning. The effect size of the tutor, 1.15, was relatively high as well—the average for computer tutors is 0.79. Qualitative focus groups revealed that participants expressed favorable views of the tutor in comparison to textbook learning. They found it more engaging and more enjoyable and reported that it effectively organized the content. The results of this study support the efficacy of a well-designed computer-based tutor for learning key concepts of trauma nursing.